DETECTING GENETIC DIVERSITY AMONG BARLEY LANDRACES GROWN IN THE WEST-BANK, PALESTINE IN 2010-2011 - M. J. Y. Shtaya; J. Abdallah; H. Al-Fares; H. Abu-Qaoud; O. A. Baker; M. V. Korf; M. Haddad (Journal of Animal and Plant Sciences, 2015)
Fifteen barley landraces were collected from different localities in the West-Bank,-Palestine during 2009. A field experiment was conducted at the Faculty of Agriculture-An Najah National University to evaluate several agronomical traits of these landraces in 2010-2011 growing season. Cluster analysis was performed using the complete-linkage method, genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), broad sense heritability (H2), and genetic advance (GA) were calculated for the quantitative traits. Significant diversity was exhibited among the landraces regarding days to 90% heading, 100- grain weight, number of grains per spike, spike length, and awns length. The Cluster analysis showed high genetic diversity among the collected landraces with dissimilarity ranging from   0.26 to   0.75. The fifteen landraces were grouped into four clusters. Genotypic coefficient of variation ranged from 6.1 to 22.9, whereas phenotypic coefficient of variation ranged from 6.6 to 41.8 with maximum phenotypic and genotypic variability observed for number of fertile tellers, number of grains per spike and spike length. Moderate to high heritability (broad sense) estimates (70-87%) were found for most of the characters. The genetic advance was highest for number of grains per spike (39.4%), followed by spike length (37.2%). High positive significant correlations were found among the different studied traits with correlation coefficient ranging from 0.395 to 0.536.  The results of this study indicated high genetic diversity among barley landraces in Palestine, which make them potential sources for selection and hybridization programmes.
Keywords: Barley landraces; Genetic diversity; Heritability; Hordeum vulgare